PENINGKATAN PERFORMANSI MANUVER GERAKAN ROLL HEXACOPTER DENGAN METODA KENDALI PID ADAPTIF - Al, Al; Premadi, Aswir; Effendi, Asnal; Alfith, Alfith; Dasman, Dasman; Syofian, Andi (ITP Press, 2023)
In the Hexacopter flight control system, there are three very influential movements, namely Pitch, Roll and Yaw movements. Roll movement is very important to note because it affects the direction of the plane's flight. This movement is strongly influenced by the system's dynamic response to changes in hardware characteristics and the influence of changes in wind direction and speed from external systems. For this reason, this research is offered to implement a control system that can adapt to these dynamic disturbances. This study proposes the application of a proportional integral derivative (PID) control system, where constant values can adjust to dynamic changes in the system. These constant values can adjust to changes in errors and delta errors at any time. then a fuzzy logic controller (FLC) algorithm is applied, to make the constant values adaptable. The design of Fuzzification and Defuzzification is based on the maximum error and delta error limits. After real-plant testing, system performance is obtained as follows: settling time = 24mS; peak time 21mS; rise time = 9mS; delay time = 4.4mS; percent overshoot and steady state error = 1%.